Simplification of HAART therapy on ambulatory HIV patients in Malaysia: a randomized controlled trial - Velvanathan T; Islahudin F; Sim BL; Taha NA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Objective: Evaluate the impact of fixed-dose combination (FDC) containing emtricitabine (FTC), tenofovir (TDF), and efavirenz (EFV) versus a free-dose combination (FRC) of the same three drugs on clinical outcomes, adherence and quality of life in Malaysian outpatients with HIV. Methods: HIV patients (n=120) on highly active antiretroviral therapy (HAART) in the infectious disease clinic of Hospital Sungai Buloh were randomized to either FDC (n=60) or FRC (n=60). Morisky scores, health-related quality of life scores and clinical outcomes such as CD4 count and viral load were assessed in both groups at baseline and six months. Result: Patients on FDC (108 SD=1.1) had a significantly higher CD4 count increase compared to the FRC group (746.1 SD=36.3 vs 799.8 SD=33.8) (p <0.001). The viral load profile was unchanged and remained undetectable in both groups. The quality of life EQ-5D scores showed a positive correlation with CD4 counts in the FDC group (ρ=0.301, p=0.019) at six months. On the other hand, quality of life EQ-VAS scores was significantly associated with medication adherence in the FDC group at six months (ρ=0.749, p=0.05). However, no significant changes or associations were observed in the FRC group. Conclusion: Management of HAART using an FDC demonstrated a positive clinical outcome, adherence and quality of life within six months in local HIV patients.